Filter media for storm water treatment in sustainable cities: A review - Westholm, Lena Johansson (Frontiers in Chemical Engineering, 2023)
Storm water treatment and management will be more important in the future due to climate changes, e.g., more frequent, and intense rain events that might cause flooding. To meet these challenges, low impact development (LID) technologies such as paved surfaces, green roofs and various bioretention systems have been suggested in urban areas. Various filter media, natural and engineered materials, have been used to amend the LID solutions in field experiments enhancing the removal of different contaminants present in storm water of different kinds. Researchers suggest locally available low-cost media having high capacity to remove pollutants. Other parameters to take into consideration when selecting filter media are clogging, hydraulic parameters. Climatic conditions in different regions, e.g., temperate, or cold climatic zones, do not seem to have a large impact on performance on LID solutions